Brinzolamide ophthalmic suspension: a review of its pharmacology and use in the treatment of open angle glaucoma and ocular hypertension - Michele Iester (Dove Medical Press, 2008)
Michele IesterClinica Oculistica, University of Genoa, ItalyAbstract: Brinzolamide is a white powder commercially formulated as a 1% ophthalmic suspension to reduce intraocular pressure (IOP). Pharmacologically, brinzolamide is a highly specific, non-competitive, reversible, and effective inhibitor of carbonic anhydrase II (CA-II), able to suppress formation of aqueous humor in the eye and thus to decrease IOP. Several clinical trials have evaluated its safety and the most commonly ocular adverse events are blurred vision (3%–8%), ocular discomfort (1.8%–5.9%), and eye pain (0.7%–4.0%). Brinzolamide has been introduced to treat ocular hypertension and primary open-angle glaucoma. In some clinical studies it has been estimated that brinzolamide reduced IOP by was about 18%. Brinzolamide can be added to beta-blockers and prostaglandins. In the latter combination, because prostaglandin derivatives improve the uveoscleral outflow but also increase the activity of CA in ciliary epithelium with a secondary increase in aqueous humor secretion, and slightly reduce the efficacy of prostaglandin analogues, theoretically topical CA inhibitors (CAI) decrease IOP by inhibiting CA-II, thus improving prostaglandin efficacy as well as lowering IOP. Brinzolamide could have a secondary possible effect on ocular flow too. Some clinical studies showed a mild improvement of ocular blood flow. Theoretically, CAI could give rise to metabolic acidosis, with secondary vasodilatation and improvement of blood flow. Systemic acidosis can occur in the setting of oral CAI therapy, and local acidosis within ocular tissues is theoretically possible with topical CAI therapy, with the potential for a local increase in ocular blood flow. In conclusion, topical CAI treatment has efficacy in IOP-lowering ranging from 15% to 20%. From published data, brinzolamide can be used as first-line medication, even if other medications have a higher efficacy, with few side effects and it is a good adjunctive treatment. In some type of glaucoma patients with a vascular dysregulation, topical CAI could have a double effect: reducing IOP and improving ocular blood flow.Keywords: brinzolamide, ocular hypertension, glaucoma, intraocular pressure, ocular blood flow, safety, treatment